Infrastructure investment in the Western Balkans: A first analysis - Mario Holzner; Monika Schwarzhappel (European Investment Bank (EIB), 2018)
This study provides a first analysis of the recent development in infrastructure investment in the Western Balkans. It identifies infrastructure gaps as well as key infrastructure initiatives in the region, outlines the political dimension and provides the respective detailed infrastructure investment data as collected from the Western Balkans statistical offices.
Keywords: 330; Infrastrukturinvestition; Öffentliche Investition; Wirtschaftswachstum; Simulation; Südosteuropa